Challenges and Dilemmas Faced by Labor Market Integration Support Providers in Portugal - Martinho, Ana Luisa (Socialinė teorija, empirija, politika ir praktika, 2024)
This research delves into the challenges and dilemmas faced by both professionals and people in vulnerable situations in the process of social and professional inclusion. Grounded in a theoretical framework that underscores the persistent rates of labor exclusion among specific social groups and the fragmented social policies in Portugal, the study aims to understand the structural framework and practices in this field.This research adopts a qualitative approach to investigate the challenges of the social and professional integration of people in vulnerable situations. For this purpose, the study employs nine in-depth case studies within the context of social economy organizations in Portugal.The findings illuminate the complex challenges faced by professionals supporting people with complex needs, including the nonlinearity and multifaceted nature of the inclusion process, resource inadequacies, the need for specialized training and guidance, and a labor market unaligned with the needs and abilities of the clients. The study underscores the necessity for a more holistic, supportive, and inclusive approach to address the intricate dynamics of social and professional integration for people in vulnerable situations.